Inflammatory pseudotumor of the liver diagnosed as metastatic liver tumor in a patient with a gastrointestinal stromal tumor of the rectum: report of a case - Matsuo, Yoichi (BioMed Central, 2014)
BACKGROUND: Inflammatory pseudotumor (IPT) of the liver is a rare benign lesion. A case of IPT of the liver found in association with a malignant gastrointestinal stromal tumor (GIST) is reported. CASE REPORT: A 74-year-old man was admitted to our hospital for a liver tumor. He previously underwent rectal amputation for a malignant GIST. Computed tomography (CT) revealed a low-density area in the liver and dynamic contrast-enhanced MRI (EOB-MRI) showed that the tumor was completely washed out in the delayed phase. (18)Fluorine-fluorodeoxyglucose positron emission tomography (FDG-PET) showed strong uptake in the liver. A diagnosis of liver metastasis was made and partial hepatectomy was performed. Microscopic examination showed that the tumor was an IPT. CONCLUSION: Differential diagnosis between IPT and malignant neoplasms is difficult. Moreover, FDG-PET revealed strong uptake in the tumor. To our knowledge, this is the first patient reported to have an IPT in association with a rectal GIST. This patient is discussed along with a review of the literature.